First report on classical biological control releases of the larval parasitoid Ganaspis brasiliensis against Drosophila suzukii in northern Italy - Lorenzo Fellin; Alberto Grassi; Simone Puppato; Alberto Saddi; Gianfranco Anfora; Claudio Ioriatti; Marco Valerio Rossi-Stacconi (BioControl, 2023)
Current management strategy of the invasive fruit fly Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) exploits different tools but relies mainly on chemical control. In the invaded areas, the local natural enemy community mostly consists of generalist pupal parasitoids unable to control the pest efficiently. Conversely, in the pest native area, there are more specialized sympatric larval parasitoids attacking D. suzukii . Following foreign explorations and quarantine risk assessments, the larval endoparasitoid Ganaspis brasiliensis (Ihering) (Hymenoptera: Figitidae) was selected as the best candidate for classical biological control programs. In 2021, the first ever propagative biocontrol program using a Japanese G1 lineage of G. brasiliensis started in Italy. Here we report the results of the first year of releases in the province of Trento (Northeast Italy), wherein G. brasiliensis was released in 12 locations. Pre- and post-release samplings on fresh and fallen fruits were performed around the release points to assess the recapture rate, the impact of the exotic parasitoid on D. suzukii and its potential interactions with local non-target species. After releases, G. brasiliensis was recovered at 50% of the locations. The exotic parasitoid only emerged from D. suzukii , mostly from fresh fruit still on the plant. Post-overwintering monitoring revealed the presence of a four G. brasiliensis individuals at two release locations.

Augmentative releases of Trichopria drosophilae for the suppression of early season Drosophila suzukii populations - Marco Valerio Rossi Stacconi; Alberto Grassi; Claudio Ioriatti; Gianfranco Anfora (BioControl, 2019)